3D Carambola‐Like CuO/TiO2 Nanotube Heterostructures via Low‐Temperature Solution Process for Photocatalytic Activity. Issue 19 (5th May 2021) - Ren, Shuai; Zhang, Jiejing; Lu, Huiqing; Gao, Shiyong; Li, Lin; Rong, Ping; Zhang, Xiaolei; Liu, Yi; Sang, Dandan
Abstract: CuO/TiO2 heterostructures have been synthesized via a facile low‐temperature solution method. The resultant heterostructures present a three‐dimensional hierarchical morphology of carambola‐like CuO integrated with TiO2 nanotubes (NTs), confirmed by means of SEM, TEM, EDS, XRD and XPS. And time‐dependent evolutions of morphology show that the CuO grow from the initial leaf‐shaped nanosheets and eventually form carambola‐like structures. The UV/Vis absorption spectrum indicates that the carambola‐like CuO/TiO2 NTs have strong absorption in the UV light region as well as in the visible light region. The study on evaluating photocatalytic activity indicates that the carambola‐like CuO/TiO2 NTs can degrade 40 % of Rhodamine B, exhibiting enhanced photocatalytic activity compared with TiO2 NTs. Moreover, the photocatalytic mechanism of the carambola‐like CuO/TiO2 NT heterostructures is expounded. Abstract : A novel 3D carambola‐like CuO/TiO2 nanotube heterostructures are synthesized. The as prepared CuO/TiO2 heterostructures exhibit higher photocatalytic performance than TiO2 nanotubes. This is mainly because the unique 3D heterostructure not only offers appropriate space to allow multiple reflections of light, but it can also effectively inhibit the recombination of electron‐hole pairs.